Evaluation and large-scale dissemination of orange-fleshed sweetpotato in SubSaharan Africa - Kapinga, R.; Zhang, D.; Andrade, M.I.; Lemaga, B.; Mwanga, R.O.M.; Tumwegamire, S.; Laurie, S.; Ndolo, P.J. (2003)
Current breeding strategies for sweetpotato in sub Saharan Africa (SSA) emphasizes: breeding orange-fleshed sweetpotato (OFSP) with high dry matter content and resistance to sweetpotato virus disease (SPVD), pathogen clean up of promising cultivars for the large scale testing, multiplication and dissemination. Breeding new sweetpotato with high dry matter and high beta-carotene was started by CIP in 1996. Research and development is carried out in collaboration with a range of institutional partners, including NARIs, universities, NGOs, farmers’ groups and community-based organizations. Rigorous evaluation and dissemination of the first batch have resulted to several varieties that are acceptable to consumers. In Kenya, varieties Zapallo, SPK 004 and Salybolo are good for high yields and good root characteristics. In Uganda, Ejumula, Kala and SPK 004 have been identified for wider adaptability in different agroecologies and desirable consumer acceptance. The same for Zapallo, Japon Tresimesino and Tainung 64 in Tanzania. In South Africa, varieties Resisto, W-19 and Excel have been selected for high dry matter, high beta-carotene content and processing onto value added products. Distribution of more than twenty promising clones has been done to Madagascar, Mozambique, Ethiopia, Uganda, Tanzania, Zimbabwe, Egypt, Zanzibar, Malawi, D.R. Congo and Sudan. Over 10 million cuttings of planting material of improved varieties were multiplied and distributed in East African region, covering over 360 hectares of farmers’ fields.